Faktor Yang Berhubungan Dengan Tingkat Kelelahan Pekerja Di PT. Industri Kapal Indonesia (Persero) - Muzhaffar, Andi Alif; Muh. Saleh Jastam; Muhammad Ikhtiar (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Fatigue is a complaint among the general public, especially the working population. Work fatigue can be characterized by a decrease in all conditions that affect all organism processes, including several factors such as feelings of work fatigue, decreased motivation, and decreased mental and physical activity. Based on data from the International Labor Organization (ILO), it states that every year, as many as two million workers die due to work accidents caused by fatigue factors. This study aimed to determine the factors related to the level of worker fatigue at PT. Industri Kapal Indonesia (Persero) in 2022. . This type of research is quantitative research using the Cross-Sectional Study method. The population in this study was all production workers at PT. Industri Kapal Indonesia (Persero) had a sample size of 44 workers, using a total sampling technique of 44 workers. The data analysis method used the Chi-Square test. The results showed no relationship between age factors and work fatigue (p value = 1,000> 0.05). Work fatigue was not related to workload factors (p value = 0.290> 0.05). There is no relationship between the length of service factor and work fatigue (p value = 0.582 >0.05). There is a relationship between the Length of Service factor and work fatigue (p value = 0.025 <0.025). There is a relationship between the Noise factor and work fatigue (p-value = 0.004 <0.004). This study suggests that companies use personal protective equipment (PPE) for employees who are in direct or indirect contact with tools that make noise to reduce the risk of exposure to noise that will cause fatigue in workers. Do not work beyond the working hours that should be and make the most of your rest time so as not to trigger work fatigue.